(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Children are vital to the nation’s present and future. Parents are usually committed to provide every advantage possible to the children in their families, and to ensure that they are healthy and have the opportunities that they need to fulfill their likely. The care of neonates in the family is governed by the family’s knowledge, awareness and cultural practices. The baby’s health, while in the womb, depends on health of the mother. But after being born, survival, health and growth depends mainly on the mother’s knowledge of child rearing practices and the immediate environment in which the family lives. The mother’s knowledge, Attitude and the practices play a crucial role in safeguard the health and enhancing the newborn’s adaptation to the environment. Basic care should be provided to the new born by the mother at home. This includes caring, feeding, basic hygiene and identification of danger signs and seeking help from health personnel whenever required. Each year nearly 7.7 million children under five years die around the world; out of which approximately 3.1 million of the newborns die during the neonatal period and almost all these (99%) deaths occur in the developing countries. According to the World Health Organization’s estimation neonatal deaths account for 45% of the under-five deaths. More than one-third of these deaths occur in the first 24 hours of birth, whereas three-quarter of the neonatal deaths takes place in the first seven days of birth.Aim: The main aim of this study was to assess the effectiveness of Teaching Programme regarding Neonatal care at home and to educating the mothers at some extent. Objectives: To assess the pre-test and post-test knowledge score regarding neonatal care at home among mothers. To assess the pre-test and post-test attitude score regarding neonatal care at home among mothers. To assess the pre-test and post-test Practice score regarding neonatal care at home among mothers. To evaluate the effectiveness of Structure Teaching Programme. To associate the mean difference before and after the level of knowledge, attitude and Practice. Methodology: The Quasi-experimental one group pre-test and post-test design was adopted. The 40 mothers were from the Hospital, Vadodara city by non-probability convenient sampling technique. The written setting permission was taken from the medical officer of Hospital for data collection. The prior consent form was also signed by the mothers for the study. The tool was developed by four sections:Section I: Socio-Demographic Data.Section II: Structured Knowledge Questionnaires.Section III: Likert Attitude Scale.Section IV: Checklist Questionnaires for Practice.The data were analyzed by using the SPSS Software. The frequency and percentage distribution are used to assess the demographic variables and the mean and standard deviation are used to describe the knowledge, attitude and Practice regarding Neonatal care at home. The paired t-test was used to compare pre and post test score, Chi-square test was used to determine the association between mean differences.Results: Out of 40 samples, 55.0% (22) belong to age 26-30 years, 70.0% (28) belong to Hindu religion, 32.5% (13) was secondary school educated, 50.0% (20) from rural area, 100.0% (40) have first delivery, 52.5% (21) income is 5001-10000 rupees, 50.0% (20) was Housewife, 45.0% (18) has vaginal delivery, 45.0% (18) belong to 7th – 14th day, 52.5% (21) was female child, 30.0% (12) has weight is 2.6 to 3.0kg. and (24) 60.0% belongs to joint family. The paired t-test value was 8.069, 3.369 and 4.127. Hence, there exists significance effectiveness on level of knowledge, attitude and practice before and after administration of structure teaching programme among mothers. There is no significant relationship between all the variables regarding Neonatal care at home after structure teaching programme among mothers.Conclusion: The study concludes that after the teaching programme intervention, 22.50% (9) mothers had moderately adequate knowledge, none of them had inadequate knowledge and 77.50% (31) had adequate knowledge regarding Neonatal care at home. 15.0% (6) mother had moderately favorable attitude, none of them had unfavorable attitude, and 85.0% (34) mother had favorable attitude. 12.5% (5) mother hadaverage Practice, none of them had poor Practice, and 87.5% (35) mothers had good Practice regarding Neonatal care at home among mothers.